Neuropsychological features in RASopathies: A pilot study on parent training program involving families of children with Noonan syndrome. Issue 4 (9th December 2022) - Montanaro, Federica Alice Maria; Alfieri, Paolo; Caciolo, Cristina; Cumbo, Francesca; Piga, Simone; Tartaglia, Marco; Licchelli, Serena; Digilio, Maria Cristina; Vicari, Stefano
Abstract: Noonan syndrome (NS) is a clinical variable multisystem disorder caused by mutations in genes encoding proteins involved in the RAS/mitogen‐activated protein kinase signaling pathway. NS is characterized by a distinctive facies, short stature, and congenital heart defects. Psychomotor delay, learning difficulties, and social deficits are also common. Furthermore, behavioral and attention problems can be reckoned as a key symptom in NS, with functioning resembling the patterns observed in attention deficit hyperactivity disorder (ADHD). The complex behavioral phenotype has great impact on the quality of life and raises demanding management issues also for patients' families. Parent management training (PMT) is recommended as first‐line treatment for ADHD; however, no study has been performed to test the efficacy of PMT in NS, thus far. The aim of this pilot study is the implementation and evaluation of a PMT dedicated to NS families. Parents of seven children with NS were recruited and underwent to a 10‐session PMT. Three different questionnaires were administered to both parents: Conners Parent Rating Scales, Parenting Stress Index Short Form (PSI‐SF), and Alabama Parenting Questionnaire (APQ). Our findings on this first small cohort of families indicate that positive perception and satisfaction about the child and the interaction with him increased in mothers after the intervention, as measured respectively by PSI‐SF difficult child (DC) and PSI‐SF parent–child dysfunctional interaction (PCDI), while mothers' level of stress decreased after the PMT, as indicated by PSI‐SF total scores. Furthermore, APQ positive parenting, which measures behaviors of positive relationship with the child, increased in mothers after the intervention. Statistical analysis on fathers' questionnaires did not show significant differences after the PMT sessions. This pilot study suggests that PMT is a promising intervention for parents of NS children with behavioral and ADHD symptoms. Changes in mothers' attitudes and distress indicate that behaviorally oriented programs may help parents to manage with NS phenotype.